Implementation of Farm Animal Control Policy in Bungku Tengah District, Morowali Regency - Sanjaya, Rahmat; Mangngasing, Nasi; Nuraisyah, Nuraisyah (International Journal of Social Science, Education, Communication and Economics, 2024)
This research aims to analyze the implementation of livestock control policies in Bungku Tengah District, Morowali Regency. The focus is to evaluate aspects of communication, disposition, resources and bureaucratic structure in implementing the policy. This research uses a qualitative method with a descriptive approach. Data collection was carried out through observation, direct interviews and documentation. The selection of informants used purposive techniques. The research results show that Regional Regulation number 6 of 2009 concerning Livestock Control has made a positive contribution in reducing the number of wild livestock. However, its implementation still faces several obstacles. The government's consistency in law enforcement needs to be improved, resource support, especially in terms of finance, is still lacking, and public awareness in the Bungku Tengah District area needs to be increased. In implementing livestock control policies, it is necessary to increase government consistency, increase resource support, and increase public awareness. Without optimal handling of these obstacles, livestock control cannot be implemented effectively.